Histological manifestations of wrist osteoarthritis and their dependence on the duration and severity of the disease - Nathalia A. Shchudlo; Tatyana A. Stupina; Shyngys K. Kuttygul (Гений oртопедии)
Introduction The possibilities of medical visualization of changes in the articular cartilage and subchondral bone in wrist osteoarthritis are limited. There are few studies devoted to its histological manifestations. The purpose f the work was to determine the relationships between histological features of wrist osteoarthritis and the duration and stage of SLAC / SNAC syndrome. Material and methods The surgical material of 12 patients who underwent resection of the proximal row of wrist bones or removal of the scaphoid bone and intercarpal arthrodesis was studied. In nine patients, the duration of the disease was shorter than four years and in three it was from 10 to 22 years. Stage I SLAC / SNAC syndrome was detected in two patients, stage II — in six, stage III — in four. Cartilage changes were assessed using the international OARSI scale, the prevalence of subchondral bone necrosis was determined semi-quantitatively (from 0 to 3 points) in 3–10 fields of microscopic views of the from each patient. Results The OARSI score varied from 1–2 to 5 points if the duration of the disease was shorter than four years and from 3–4 to 4–5 points if it continued from 10 to 22 years. The osteonecrosis score in the compared subgroups was 3 (2÷3)(0–3) and 3 (2÷3)(2–3), p = 0.11. In SLAC / SNAC stage I, the OARSI score variability ranges from 1–2 to 4, in stage II — from 2 to 4–5, in stage III — from 3–4 to 5. The osteonecrosis score in the compared subgroups was 2 (1÷2)(1–3), 3 (2÷3)(1–3), and 3 (2÷3)(0–3) (P1-2 = 0.03; P2-3 = 0.62; P1-3 = 0.02). Discussion The SLAC / SNAC syndrome can be of two types, progressive and stagnant. In the second type, the disease is asymptomatic for a long time. Regardless of the cause of SLAC / SNAC syndrome, all patients with wrist osteoarthritis experience irreversible osteonecrosis of the subchondral bone and bone marrow, which probably reflects the degree of acute or chronic damage to the vessels that feed the bone. Conclusion With a general tendency for greater degenerative changes in the articular cartilage at a higher stage of SLAC / SNAC syndrome, their histological manifestations vary between individuals at each stage. Osteonecrosis of the subchondral bone is more common in SLAC / SNAC stages II–III than in stage I.